Elevated pulse pressure and cardiovascular risk associated in Spanish population attended in primary care: IBERICAN study - Moyá-Amengual, Ana; Ruiz-García, Antonio; Pallarés-Carratalá, Vicente; Serrano-Cumplido, Adalberto; Prieto-Díaz, Miguel Ángel; Segura-Fragoso, Antonio; Cinza-Sanjurjo, Sergio; , the researchers of the IBERICAN study; García, Alfonso Barquilla; Rodríguez, Ángel Díaz; Cervantes, Carlos Escobar; Moreno, Francisco Javier Alonso; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Elevated pulse pressure (ePP) is an independent marker of cardiovascular risk (CVR) in people older than 60, and a functional marker of subclinical target organ damage (sTOD) which can predict cardiovascular events in patients with hypertension (HTN), regardless of sTOD. Objective To evaluate the prevalence of ePP in adult population seen in primary care and its association with other vascular risk factors, sTOD and with cardiovascular disease (CVD). Materials and methods Observational multicentre study conducted in Spain (8,066 patients, 54.5% women) from the prospective cohort study IBERICAN recruited in Primary Care. Pulse pressure (PP) was defined as the difference between the systolic blood pressure (SBP) and the diastolic blood pressure (DBP) ≥60 mmHg. Adjusted (for age and sex) ePP prevalence were determined. Bivariate and multivariate analyses of the possible variables associated with ePP were carried out. Results The mean of PP was 52.35 mmHg, and was significantly higher (p < 0.001) in patients with HTN (56.58 vs. 48.45 mmHg) The prevalence of ePP adjusted for age and sex was 23.54% (25.40% men vs. 21.75% women; p < 0.0001). The ePP prevalence rates increased linearly with age (R2 = 0.979) and were significantly more frequent in population aged ≥65 than in population aged <65 (45.47% vs. 20.98%; p < 0.001). HTN, left ventricular hypertrophy, low estimated glomerular filtration rate, alcohol consumption, abdominal obesity, and CVD were independently associated with ePP. 66.27% of patients with ePP had a high or very high CVR, as compared with 36.57% of patients without ePP (OR: 3.41 [95% CI 3.08–3.77]). Conclusions The ePP was present in a quarter of our sample, and it was increased with the age. Also, the ePP was more frequent in men, patients with HTN, other TOD (as left ventricular hypertrophy or low estimated glomerular filtration rate) and CVD; because of this, the ePP was associated a higher cardiovascular risk. In our opinion, the ePP is an importer risk marker and its early identification lets to improve better diagnostic and therapeutic management.